Stubbtransporter - en jämförelse av tre olika transportsystem - Noro Larsson, Karl (2011)
In Sweden, the demand for bio energy has increased in recent years due to the current energy and climate debate. In 2008, the energy supply of Sweden was 612 TWh, biofuels accounted for 123 TWh of these. Stumps have been highlighted as a potential fuel in recent years and the Swedish Forest Agency expects a technically and biologically feasible potential of 20.7 TWh annually between 2010 and 2019. The idea of utilize stumps is not new. During the 19th century stumps were used for tar production and during the 70’s and 80’s attempts were made to use stumps in the pulp industry. Recent tests with stump lifting for energy use have been done within the Project Bioenergy Farms which runs from 2008 to 2011. Norra Skogsägarna (a forest owners association in he north of Sweden) has had the responsibility for these tests within the project.